2020
DOI: 10.3390/app10196975
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Effect Versus Mesopic Vision Effect in Road Lighting Applications

Abstract: Several models on the circadian effect have been applied to indoor circadian lighting design, but applications in road lighting have not yet been clarified. Based on existing models and circadian research, we examined equivalent melanopic lux (EML), circadian light (CLA), and circadian stimulus (CS) representing the circadian effect and the S/P ratio representing the mesopic vision effect, among a dataset of light sources at photopic adaptation illuminance values of 1, 3, 10, 30, and 100 lx. The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In an investigation of a method to evaluate the nonvisual potential of daylight in two European cities, CCTs between 4631 K and 11,871 K were recorded in Naples and CCTs between 3585 K and 9812 K were recorded in Bialystock [17]. These results are similar to those of this study since our CCT measurements vary between 4892 and 12,380 K. However, due to the low correlation between the CCT and circadian effects, it is considered that the CCT is not a good indicator to establish the levels of circadian response [20,37]. Although Rea et al reported that LEDs with high CCTs above 5299 k could slightly stimulate the circadian system after one hour of exposure to outdoor lighting at 95 lux, when taking advantage of natural light in interior spaces, the reflectance of the walls must also be considered because they vary the CCT and the spectral composition of light that regulate the circadian system [38][39][40].…”
Section: Circadian Characteristicssupporting
confidence: 87%
See 1 more Smart Citation
“…In an investigation of a method to evaluate the nonvisual potential of daylight in two European cities, CCTs between 4631 K and 11,871 K were recorded in Naples and CCTs between 3585 K and 9812 K were recorded in Bialystock [17]. These results are similar to those of this study since our CCT measurements vary between 4892 and 12,380 K. However, due to the low correlation between the CCT and circadian effects, it is considered that the CCT is not a good indicator to establish the levels of circadian response [20,37]. Although Rea et al reported that LEDs with high CCTs above 5299 k could slightly stimulate the circadian system after one hour of exposure to outdoor lighting at 95 lux, when taking advantage of natural light in interior spaces, the reflectance of the walls must also be considered because they vary the CCT and the spectral composition of light that regulate the circadian system [38][39][40].…”
Section: Circadian Characteristicssupporting
confidence: 87%
“…According to Rea, the daylight spectrum has been shown to be relatively efficient in providing circadian stimulation; and based on the CIE D 65 spectrum, a corneal illuminance of 233 lx corresponds to this 0.35 CS. Extrapolating our outdoor analysis to indoor situations, circadian efficiency should be treated with caution because artificial lighting seems to be less effective since for the same value of CS = 0.35, a corneal illuminance much higher than that necessary with natural light would be needed [37]. All the outdoor SPDs collected for this paper are, regarding the CCT, above 4800 K, meaning that for indoor lighting purposes, it would be equivalent to cold light; and, assuming the same light intensity, higher CCT values indicate a greater perception of luminosity.…”
Section: Circadian Characteristicsmentioning
confidence: 99%
“…Other luminance levels occur in the case of the observed substrate being illuminated by lanterns. As reported in [79,80], when road lighting is considered, the luminance is usually in the range from 0.5 to 2 cd/m 2 . It is of significant practical importance because the spectral sensitivity of the eye changes with the change of luminance, which is graphically illustrated in Figure 6.…”
Section: Uncovered Light Sourcesmentioning
confidence: 99%
“…According to the CIE recommendations [81], it is assumed that the scotopic state of vision occurs at a luminance ≤ 0.005 cd/m 2 , while photopic vision occurs at a luminance value ≥ 5 cd/m 2 . Photopic and scotopic vision extends the range of mesopic vision, which was studied, for example, in [5,80,[82][83][84][85]. The general conclusion from these works is that additional savings can be achieved when te LED sources are used to illuminate parks in terms of the mesopic effect.…”
Section: Uncovered Light Sourcesmentioning
confidence: 99%
“…It is known that high-quality street lighting improves visual perception of the road and provides for a significant decrease in the number of road accidents. It has been established that the total number of accidents can be reduced by 30% for national roads and by 45% for especially hazard areas (e.g., at intersections) [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%